Hepatocyte ABCA1 deficiency is associated with reduced HDL sphingolipids - Othman, Alaa; Liu, Mingxia; Bode, Heiko; Boudyguina, Elena; von Eckardstein, Arnold; Parks, John S.; Hornemann, Thorsten (Frontiers in Physiology, 2023)
ATP binding cassette transporter A1 (ABCA1) limits the formation of high density lipoproteins (HDL) as genetic loss of ABCA1 function causes virtual HDL deficiency in patients with Tangier disease. Mice with a hepatocyte-specific ABCA1 knockout (Abca1 HSKO) have 20% of wild type (WT) plasma HDL-cholesterol levels, suggesting a major contribution of hepatic ABCA1 to the HDL phenotype. Whether plasma sphingolipids are reduced in Tangier disease and to what extent hepatic ABCA1 contributes to plasma sphingolipid (SL) levels is unknown. Here, we report a drastic reduction of total SL levels in plasma of a Tangier patient with compound heterozygosity for mutations in ABCA1. Compared to mutation-free controls, heterozygous mutations in ABCA1 had no significant effect on total SLs in plasma; however, apoB-depleted plasma showed a reduction in total SL also in het carriers. Similarly, liver specific Abca1 KO mice (Abca1 HSKO) showed reduced total sphingolipids in plasma and liver. In parallel, apoM and sphingosine-1-phosphate (S1P) levels were reduced in plasma of Abca1 HSKO mice. Primary hepatocytes from Abca1 HSKO mice showed a modest, but significant reduction in total SLs concentration compared to WT hepatocytes, although SL de novo synthesis and secretion were slightly increased in Abca1 HSKO hepatocytes. We conclude that hepatic ABCA1 is a signficant contributor to maintaining total plasma pool of HDL sphingolipids, including sphingomyelins and S1P.